State of Art and Perspective of Calcium Phosphate-Based Coatings Coupled with Bioactive Compounds for Orthopedic Applications - Matteo Montesissa; Viviana Tommasini; Katia Rubini; Marco Boi; Nicola Baldini; Elisa Boanini (Nanomaterials)
The aim of this review is to investigate the possibility of fabricating coatings functionalized with bioactive molecules. These coatings are interesting when applied to biomedical devices, particularly in the orthopedic field. In fact, the application of calcium phosphate-based coatings on the surface of implanted devices is an effective strategy to increase their osteoinductive and osseointegrative properties. Several coating fabrication technologies are presented, including chemical deposition and physical methods. The application of bioactive molecules in combination with calcium phosphate coatings may improve their osteointegrative, antibacterial, and antitumor properties, therefore increasing the performance of implantable devices.